Returning to Babel Jewish Latin American experiences, representations, and identity - Ran, Amalia; Cahan, Jean Axelrad (Leiden : BRILL, 2011)
This edited volume explores multiple representations by and of Jewish Latin Americans, thus revisiting the canon of Judeo-Latin American culture. It expands the horizon of what is traditionally considered "Jewish" or "Latinoamericano."
List of Figures and Tables; Acknowledgements; List of Contributors; Introduction Rethinking Jewish Identity in Latin America; Part One Jewish Latin American Experiences, Past and Present; Part Two Jewishness as Literary Representation; Part Three Jewish and Lo Latinoamericano in the Arts; Part Four The Notion of Otherness and the Question of Integration; Bibliography; Index.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Jews -- Latin America -- Identity; Jews -- Latin America -- Intellectual life -- 21st century; Jews -- Latin America -- Social life and customs; Jews -- Cultural assimilation -- Latin America; Social integration; Latin American literature -- Jewish authors -- History and criticism; Jewish literature -- Latin America -- History and criticism; Jewish literature -- Latin America -- History and criticism; Jews -- Cultural assimilation -- Latin America; Jews -- Latin America -- Identity; Jews -- Latin America -- Intellectual life -- 21st century; Jews -- Latin America -- Social life and customs; Latin American literature -- Jewish authors -- History and criticism; Social integration; HISTORY / Latin America / General; HISTORY / Latin America / South America; Electronic books